What is popular Islam? Towards a Critical Genealogy of the Concept and its Relationship with the Disctinctions Orthodoxy/Heterodoxy and Orthopraxy/Heteropraxy - González Vásquez, Araceli (2018)
The concept of "popular Islam" has a wide predicament in the academic literature generated by the Social Sciences and the Humanities, and also, in general, in contemporary media discourses on Islam and Muslims, and it is used particularly in order to characterise certain religious beliefs and practices. In the present article, centered on examples related to North Africa and, specifically, to Morocco, I will try to present a critical genealogy of this concept, and I will try to reflect on its relationship with the distinctions orthodoxy / heterodoxy and orthopraxis / heteropraxis.